Encenações narrativas do arquivo público e pessoal: fricções-ficções (João Tordo, Orhan Pamuk, Chico Buarque) - Nathalia de Aguiar Ferreira Campos (2020)
This thesis examines the narrative staging of the archive in a quartet of contemporary fictions: Three Lives (2008) and The Anatomy of Martyrs (2011), by João Tordo, The Museum of Innocence (2008), by Orhan Pamuk, and My German Brother (2015), by Chico Buarque. Taking the phenomenon of insistence of the compositional element of the archive in fictional production as its kick-off, this analysis groups narratives that, by the common presence of the archive (brought up in its figures, namely document, collection, museum, encyclopaedia, among others), reflect issues such as the obsession by the constitution of memories in the presentistic context, and allow to assess the commitment or lack of commitment of the archive with the monumental and/or already told stories. Therefrom, the research navigates through some central topics: mise en archive – archival figures (modalities), characters and their roles before the archive; antagonistic situations of relationship with it, called frictions (tension/dysphoria X affinity/euphoria), according to the operating meanings of history in the narratives and the public and personal spheres of the archive; commitments assumed by the fictional narrative with the opening of historiographic making, from fissures in conventional approaches and from excuses and objects marginalized in them; statutes of fiction and reality/truth in the fictions examined. In view of some recurrences in such representations of the aesthetic and epistemological figure of the archive, it is also sought to verify the hypothesis of a category or lineage for such fictions (fictions of the archive), considering the various existing possibilities of articulation between the domains of meaning of archive and fiction.